UPAYA PENEGAKAN HUKUM TERHADAP TINDAK PIDANA AKSES TANPA HAK DIHUBUNGKAN DENGAN UNDANG-UNDANG UNDANG NOMOR 19 TAHUN 2016 ATAS PERUBAHAN UNDANG-UNDANG NOMOR 11 TAHUN 2008 TENTANG INFORMASI DAN TRANSAKSI ELEKTRONIK - Bambang Meiryawan (Scientia Regendi, 2020)
Crime develops along with the advancement of human civilization, information technology crime has developed along with the development of Information Technology, one of which is the criminal act of illegal access which is very detrimental to others, due to illegal access this can cause enormous losses both financially and non-financially. in the case of ticket.com burglary, the owner of the server was harmed worth 5 (five) billion rupiah, and many criminal cases of illegal access were very detrimental, including burglary on the KPU website, burglary of servers belonging to other government institutions, based on this background the authors found several problems for appointed in this study, namely How is the regulation of illegal access in Indonesia regulated in Law Number 19 of 2016 concerning Amendments to Law number 11 of 2008 concerning Information and Electronic transactions? Legal Measures That Police Can Do In Anticipating Crimes of Illegal Access That Occur In Indonesia? The author conducted a study using the Normative juridical approach method by analyzing the articles in the legislation with the problems studied. The nature of the research is descriptive analysis, which is to provide data as thoroughly as possible about the situation or symptoms that are the object of research. The stages of research are carried out through library research to obtain secondary data derived from primary legal materials, secondary legal materials, tertiary legal materials and through field research, namely data analysis without using formulas and numbers. From the results of the research, it was concluded that the regulation regarding illegal access is regulated in Article 30 of the ITE Law, then Article 32 of the ITE Law. Article 33 of the ITE Law. Weaknesses in server management are one of the causes of the collapse of the information system from attacks on illegal access, prosecutors in the case of Tiket.com should be more careful because the elements of money laundering have been fulfilled with the elements accompanied by available evidence. The need for evaluation of policies in cybercrimes is still needed if there are weaknesses in the formulation policy in the legislation. This evaluation or review needs to be done, because there is a close relationship between the policy formulation of legislation (legislative policy) with law enforcement policies (law enforcement policy) and policies on crime/crime (criminal policy).